Financing for Development : Using Independent Evaluation to Turn Aspirations into Achievements - Independent Evaluation Group (World Bank, Washington, DC, 2015)
The development community is increasingly accepting the importance of evidence, feedback, and learning. Some of which is generated through research, monitoring, and self-evaluation during policy-making, program design, and implementation. Others come from feedback from people directly affected by interventions who have gained a greater voice, be it through third-party feedback mechanisms, social media, beneficiary surveys, or otherwise. And, there is independent evaluation. At the World Bank Group, the independent evaluation group (IEG) has over the past years deepened the evidence that can help development finance succeed in translating the sustainable development goals (SDGs) into actions and results. This paper brings together insights from a cross-section of relevant evaluations that cover various aspects of the large, multifaceted agenda of the SDGs and their financing needs.